Human leukocyte antigen associations with acute leukemia: An indian perspective - Hina Solanki; Vikash C Mishra; Aseem K Tiwari; Nipun Kakkar; Naveen Vashisht; Vimarsh Raina; Girish Sharma (Indian Journal of Medical and Paediatric Oncology)
Objective: Acute lymphoid leukemia (ALL) and acute myeloid leukemia (AML) are neoplastic blood disorders in which the cancerous white blood cells accumulate, resulting in a significant morbidity and mortality. Human leukocyte antigen (HLA) association is observed as one of the factors in the development of leukemia. The objective of the present study was to analyze the allele frequency of HLA Class I (HLA-A, HLA-B, and HLA-C) and Class II (HLA-DRB1 and HLA-DQB1) in Indian acute leukemia patients and to compare them with the frequencies in healthy, unrelated Indian individuals. Materials and Methods: We included 500 Indian leukemic patients (AML = 324 and ALL = 176) and 1000 unrelated, healthy, Indian individuals as controls. The HLA typing was performed using polymerase chain reaction with sequence-specific oligonucleotide probes. Results: On univariate analysis, allele frequencies of HLA-AFNx0111 and HLA-DRB1FNx0111 were lower in patients with ALL (P = 0.0181 and P = 0.0025, respectively). Whereas of HLA-AFNx0111, HLA-DRB1FNx0111, and HLA-BFNx0151, these frequencies were relatively lower in patients with acute leukemia (AML + ALL) (P = 0.0382, P = 0.0093 and P = 0.0384, respectively) and HLA-CFNx0101 (P = 0.0304) in AML when compared with control individuals. In contrast, the HLA-BFNx0139 and HLA-CFNx0107 allele frequency was higher in acute leukemia (P = 0.00372 and P = 0.0463, respectively) and in AML (P = 0.0010 and P = 0.0178, respectively) than that in controls. On multivariate analysis, BFNx0139 showed positive associations with acute leukemia (P = 0.006) and AML (P = 0.002). HLA-AFNx0111 and-DRB1FNx0111 showed a negative association with acute leukemia (P = 0.009 and P < 0.0001, respectively) and ALL (P = 0.013 and P < 0.0001, respectively). Conclusions: The HLA-BFNx0139 has a positive association with AML and acute leukemia, whereas HLA-AFNx0111 and HLA-DRB1FNx0111 alleles have negative association with ALL and HLA-BFNx0151 along with these two alleles with acute leukemia. No positive association was observed with ALL. HLA-CFNx0101 frequency was lower in AML patients than that in controls.